0
$\begingroup$

Suppose $g(z)$ is analytic at $z_0$. Proof $g(z)$ has zero of order $m$ at $z_0$ iff $ lim_{z\rightarrow z_0} \frac{g(z)}{(z-z_0)^m} \neq 0$.

Sketch:

We have that $g(z)=\sum_{n\rightarrow\infty} a_n(z-z_0)^n$ If g(z) has zero of order m at $z_0$ then $\frac{g(z)}{(z-z_0)^m}=a_m+...$ Therefore $ lim_{z\rightarrow z_0} \frac{g(z)}{(z-z_0)^m} = a_m \neq 0$

If $ lim_{z\rightarrow z_0} \frac{g(z)}{(z-z_0)^m}=l \neq 0$

Def: $h(z)=\frac{g(z)}{(z-z_0)^m}$ at $z\neq z_o$ and $h(z_0)=l$

Since $lim_{z\rightarrow z_0} h(z)$ exists $h(z)$ has removable singularity at $z_0$

Hence $h(z)=\sum_{n\rightarrow\infty} a_n(z-z_0)^n$ where $a_1=l$ which implies that $g(z)=\sum_{n\rightarrow\infty} a_n(z-z_0)^{m+n}$

Hence $ g(z)$ has zero of order m at $z_0$

Is the proof valid?

$\endgroup$
  • $\begingroup$ How do you define a zero of order $m$? $\endgroup$ – José Carlos Santos Oct 20 '18 at 6:31
  • $\begingroup$ the smallest m such that a_m is not zero $\endgroup$ – Jhon Doe Oct 20 '18 at 6:36
2
$\begingroup$

Your proof is correct, but you can prove it without using the concept of removable singularity.

Suppose that $z_0$ is not a zero of order $m$. There are then $3$ possibilities:

  1. $z_0$ is not a zero of $g$. Then, since $\lim_{z\to z_0}(z-z_0)^m=0$, the limit $\lim_{z\to z_0}\frac{g(z)}{(z-z_0)^m}$ doesn't exist (in $\mathbb C$).
  2. $z_0$ is a zero of order $k<m$. Then$$\lim_{z\to z_0}\frac{g(z)}{(z-z_0)^m}=\lim_{z\to z_0}\frac{g(z)}{(z-z_0)^k(z-z_0)^{m-k}}=\lim_{z\to z_0}\frac{\frac{g(z)}{(z-z_0)^k}}{(z-z_0)^{m-k}},$$ which, again, doesn't exist (in $\mathbb C$).
  3. $z_0$ is a zero of order $k>m$. Then a similar computation shows that the limit does exist, but it is equal to $0$.
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.